Supracondylar humerus fractures in infants and toddlers: an unexplored area - Kow, Ren Yi; Low, Chooi Leng; Awang, Mohd Shukrimi (Taylor & Francis, 2022)
This write-up refers to the article ‘Supracondylar Humerus Fractures in Infants and Early Toddlers: Characteristics, Clinical and Radiological Outcomes Compared With Older Children’.